SLAVERY SHOWN THROUGH THE PRESUPPOSITIONS OF THE CHARACTERS IN THE MOVIE HARRIET (2019) - Baiq Intan Pertiwi; Ni Made Widisanti S; Sari Rejeki (Journal Albion : Journal of English Literature, Language, and Culture, 2021)
The purpose of this study is to describe the presupposition and common ground of the movie Harriet which was released in 2019. This study uses a qualitative research with descriptive analysis method. The data source of this study is obtained from the script of the movie. The data analyzed are utterances between the movie characters which contain presupposition elements. This study is executed by using the discourse perspective of slavery. The result shows that there are 17 data containing presupposition; 5 counter-factual presuppositions, 5 potential presuppositions, 5 structural presuppositions and 2 factive presuppositions. These result indicate that there are only 4 types of presuppositions found in this study while the other 2 types of presuppositions (lexical and non-factive presuppositions) even though they contain presuppositions, there is no element of slavery in them. From this research, it can be concluded that presuppositions depict the discourse of slavery that surrounds the movie.Keywords: presupposition; common ground; discourse of slavery; movie.